A STUDY ON THE FINANCIAL PERFORMANCE OF SELECTED BANKS IN KARNATAKA INDIA - Deepu B, Deepu B ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2024)
In every way, banking is crucial to the expansion and development of the Indian economy. The study's primary goal is to use the CAMEL grading methodology to compare and assess the financial performance of a few selected banks. Secondary information required for the study was gathered from annual reports of the banks, bulletins, periodicals, newsletters, internal bank reports, journals, magazines, and websites. The CAMEL framework has been used to analyse the collected data. ICICI Bank, HDFC Bank, YES Bank, AXIS Bank, and FEDERAL Bank are the banks chosen for analysis. The chosen banks were studied during the years of 2015 to 2019. The study reveals that HDFC Bank and AXIS Bank are the best banks based on the overall grade of the CAMEL analysis